Morphological and elemental mapping of gallstones using synchrotron microtomography and synchrotron X‐ray fluorescence spectroscopy. Issue 5 (29th March 2019) - Bakthavatchalam, Mohana; Venkataraman, Jayanthi; Ramana, Ramya J; Jain, Mayank; Singh, Balwant; Thanigai, Arul K; Velyoudam, Vaithiswaran; Manickam Neethirajan, Saravanan; Tiwari, Manoj K; Agarwal, Ashish K; Kalkura, Narayana S
Abstract : Background and Aim: Regional differences in gallstone (GS) composition are well documented in the Indian subcontinent. The reasons for the same are unknown. Etiopathogenesis of GS remains elusive despite advances in instrumentation. This was an in‐depth analysis of the chemical, structural, and elemental composition of GS with special reference to synchroton studies. Methods: We used high‐end sensitive analytical complementary microscopic and spectroscopic methods techniques, such as X‐ray diffraction, scanning electron microscopy, Fourier transform infrared, synchrotron X‐ray fluorescence spectroscopy (SR‐XRF), and 2D and 3D synchrotron microtomography (SR‐μCT), to study the ultra structure and trace element composition of three major types of GS (cholesterol, mixed, and pigment). SR‐XRF quantified the trace elements in GS. Results: The cholesterol GS (monohydrate and anhydrate) were crystalline, with high calcium content. The pigment GS were amorphous, featureless, black, and fragile, with high calcium bilirubinate and carbonate salts. They had the highest concentration of iron (average 31.50 ppm) and copper (average 92.73 ppm), with bacterial inclusion. The mixed stones had features of both cholesterol and pigment GS with intermediate levels of copper (average 20.8 ppm) and iron (average 17.78 ppm). Conclusion: SR‐μCT has, for the first time, provided cross‐sectional computed imaging delineating the framework of GS and mineral distribution. It provided excellent mapping of cholesterol GS. SR‐XRF confirmed that pigment GS had high concentrations of copper and iron with bacterial inclusions, the latter possibly serving as a nidus to the formation of these stones. Abstract : Synchrotron microtomography (SR‐μCT) has, for the first time, provided cross‐sectional computed imaging delineating the framework of gallstone (GS) and mineral distribution. SR‐μCT provided excellent mapping of cholesterol GS, while additional synchrotron X‐ray fluorescence spectroscopy was required for quantifying elemental components in amorphous pigment and mixed GS.